Uso y aprovechamiento de especies vegetales en la Reserva Natural Miraflor, Estelí - Tórrez Luna, I.M.; Blandón Rizo, J. del S.; Castro Martin, G.R. Asesor (Managua (Nicaragua), 2000)
Sumarios (Es, En)
Ilus.; 14 ref.
Tesis (Ing Agr)
Keywords: RESERVAS NATURALES; RECURSOS FORESTALES; ESPECIES; ZONAS CLIMATICAS; COOPERATIVAS; NICARAGUA; ESTELI; MIRAFLOR